Numerical analysis of marine riser vortex-induced vibration with helical strake suppression device / Diniesh Naidu Thannimalai - Diniesh Naidu, Thannimalai (2019)
Since offshore drilling rig is exploring oil and gas into depth water and marine riser facing the problem of vortex induced vibration (VIV) due to sea current. This VIV cause the marine riser to vibrate leads to failure. One of the way to reduce the vibration by attached helical strakes at marine riser to reduce the occurrence of vortex shedding. In this research report was studied about the numerical analysis of marine riser vortex-induced vibration with helical strake of suppression device. On this study, two types of models generated which are two dimensional and three dimensional. Each one has two models to be simulated which are laminar and Turbulence for two dimensional; with and without helical strake models for three dimensional. The Lift and Drag coefficient was simulated by analyzing the flow passes through a marine riser using ANSYS software. The results obtained from ANSYS are used as the input to MATLAB for produced results in a graph. The simulation was done for two models with and without helical strake. The model with helical strake was disturbed the vortex shedding at downstream, so the vibration of marine riser reduced. The results show the model with helical has decreased the Lift coefficient up to 96%.